ChemInform Abstract: Magnetic Interactions: a Tool to Modify the Magnetic Properties of Materials Based on Nanoparticles. Issue 49 (December 2015) - Peddis, Davide; Joensson, Petra F.; Laureti, Sara; Varvaro, Gaspare
Abstract: Review: 190 refs.